2016
DOI: 10.1016/j.jacc.2016.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Variant Angina Manifesting as Aborted Sudden Cardiac Death

Abstract: The prognosis of patients with variant angina with ASCD was worse than other patients with variant angina. In addition, our findings supported ICDs in these high-risk patients as a secondary prevention because current multiple vasodilator therapy appeared to be less optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 29 publications
3
86
0
2
Order By: Relevance
“…Takagi et al showed that the incidence of cardiac death was significantly increased in patients for whom medications were reduced or discontinued 8. As shown in Figure 7A, the incidence of VF recurrence in the CAS group is consistent with that reported in previous studies 8, 21. In the current study (Figure 7B), 3 symptomatic patients with CAS experienced VF recurrence, with 2 of those experiencing VF recurrence after discontinuation of antianginal therapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Takagi et al showed that the incidence of cardiac death was significantly increased in patients for whom medications were reduced or discontinued 8. As shown in Figure 7A, the incidence of VF recurrence in the CAS group is consistent with that reported in previous studies 8, 21. In the current study (Figure 7B), 3 symptomatic patients with CAS experienced VF recurrence, with 2 of those experiencing VF recurrence after discontinuation of antianginal therapy.…”
Section: Discussionsupporting
confidence: 90%
“…13 However, patients with CAS with aborted sudden cardiac arrest have been linked to a poor prognosis compared with those without such a condition. 8,21 Ahn et al demonstrated that patients with CAS with a history of aborted sudden cardiac death remain at high risk despite antianginal therapy. 21 They reported that the annual incidence rate of recurrent ventricular tachyarrhythmia was %3%.…”
Section: Vf Recurrence and Treatment Of Ers And Casmentioning
confidence: 99%
“…Consistent with this finding, a previous study showed that systemic hypertension was a predictor of major coronary evens in VA patients in a multivariable analysis6. Another study also showed that more advanced age, hypertension and dyslipidemia were independent predictors of sudden cardiac death in VA patients16. However, a contradicting result indicated that traditional risk factors such as hypertension, diabetes mellitus and hypertension did not affect VA prognosis26.…”
Section: Discussionmentioning
confidence: 66%
“…The incidence of VA mortality has been reported by several studies67111213141516171819202122. However, those reports were limited in size and/or duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation